2013
DOI: 10.1002/ejoc.201301161
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Diversely Substituted Triarylmethyl Radicals by the Quenching of Tris(2,3,5,6‐tetrathiaaryl)methyl Cations with C‐, N‐, P‐, and S‐Nucleophiles

Abstract: C-, N-, P-, and S-nucleophiles reacted with symmetrical tris(2,3,5,6-tetrathiaaryl)methyl cations, generated from the corresponding triarylmethanols by strong acids, to give a variety of asymmetrical monosubstituted persistent triaryl-methyl (TAM) radicals as the major products. The only byproducts were symmetrical TAMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…In most cases, trityls are not so easy to synthesize, but recently a convenient way of preparing Finland trityl (Rogozhnikova et al, 2013) and diversely substituted trityls were proposed (Scheme 8A), which is based on the quenching of tris(2,3,5,6-tetrathiaaryl)methyl cations by C-, N-, P-, and S-nucleophiles (Scheme 8B) (Tormyshev et al, 2014). The authors found that C-, N-, P-, and S-nucleophiles react with symmetrical tris(2,3,5,6-tetrathiaaryl)methyl cations generated from the corresponding triarylmethanols by strong acids.…”
Section: Synthesis Of Trityl-based Spin Probes and Labelsmentioning
confidence: 99%
“…In most cases, trityls are not so easy to synthesize, but recently a convenient way of preparing Finland trityl (Rogozhnikova et al, 2013) and diversely substituted trityls were proposed (Scheme 8A), which is based on the quenching of tris(2,3,5,6-tetrathiaaryl)methyl cations by C-, N-, P-, and S-nucleophiles (Scheme 8B) (Tormyshev et al, 2014). The authors found that C-, N-, P-, and S-nucleophiles react with symmetrical tris(2,3,5,6-tetrathiaaryl)methyl cations generated from the corresponding triarylmethanols by strong acids.…”
Section: Synthesis Of Trityl-based Spin Probes and Labelsmentioning
confidence: 99%
“…Despite this progress, surprisingly little has been reported on the synthesis of monofunctional trityl derivatives, 9 especially those which possess a specific reactive functional group to enable expanded use of TAMs. These monofunctional TAM derivatives enable the X substituent, Figure 1, to control properties of the TAM core, e.g.…”
mentioning
confidence: 99%
“…9 In particular, the reaction of methyl thioglycolate with the cation 1 readily produced the functionalized TAM 2 (41%) along with two less-abundant byproducts – the unsubstituted TAM 3 and the quinonemethide 4 . This set of reactions is the basis for synthesis of one biradical.…”
mentioning
confidence: 99%
See 2 more Smart Citations